Daily reciprocal relations between negative and positive emotion dysregulation and posttraumatic stress symptoms among individuals with a history of sexual assault. (September 2022) - Raudales, Alexa M.; Yang, Manshu; Forkus, Shannon R.; Kiefer, Reina; Weiss, Nicole H.
Highlights: Negative emotion dysregulation predicts next-day posttraumatic stress symptoms. Similar findings emerge for positive emotion dysregulation. Results highlight nuances of within- and between-individual relations. Abstract: Posttraumatic stress symptoms (PTSS) are a debilitating health concern that can develop following sexual assault. One factor central to PTSS is emotion dysregulation. However, little is known about how emotion dysregulation, particularly the dysregulation of positive (versus negative) emotions, relates to the maintenance of PTSS over time. This study aimed to address this gap in the literature by using a micro-longitudinal approach to examine daily reciprocal relations between negative and positive emotion dysregulation and PTSS. Participants were 121 individuals with a history of sexual assault ( Mage  = 35.27; 70.2% women; 81.0% white) recruited from the community. Participants self-reported on negative and positive emotion dysregulation as well as PTSS once daily for seven days. Findings provide support for the effects of both negative and positive emotion dysregulation on increases in next-day PTSS. Results carry important implications for PTSS assessment and intervention efforts among those with a history of sexual assault.